Causes of Conflict in Organizations: A Case of Takoradi Polytechnic - Morrison, Sarah; ., Samuel Sundong (Journal of Education and Vocational Research, 2014)
The study explored the various causes of conflicts in organizations. The objectives of the study was to find out the nature, types and factors that lead to staff related conflicts in organizations especially tertiary educational institutions. To achieve the objectives, researchers employed the case study approach using Takoradi Polytechnic as the case study. It also involved the use of interview and questionnaire as the data collection instruments for the study. Researchers used the purposive and simple random sampling techniques to select the respondents. A sample size of 276 out of 736 of the population was selected for the study. This constitutes (36%) of the population. The sample was made up of 109 junior staff, 96 senior staff and 71 senior members. These three groups of staff from different departments were randomly and purposively invited to participate in the study. The study would be of immense benefit to management of institutions especially educational institutions since it would inform them of possible conflict that could arise. It would also inform policy formulation and staff training and development programs. It was discovered after the study that there were various conflicts in the organization which could be grouped into intra-personal, interpersonal and inter-group conflicts. These were as a result of the competing for limited resources, power struggle, differences in behavior among others. It recommends the education of staff through workshops and seminars on the differences that leads to conflicts, provision of resources and infrastructure that could mitigate the competition of resources among others.